Resilience Strategies in Moroccan Artisanal Supply Chain Networks - Hasnaoui, Lamiae; Lebbar, Sara (European Scientific Journal, ESJ, 2025)
This study examines the resilience strategies employed by Moroccan artisans within cooperative and traditional business supply chain networks, analyzing how these networks navigate disruptions while ensuring livelihoods and preserving cultural heritage. Adopting an inductive approach, the research utilizes the Gioia methodology to analyze qualitative data from semi-structured interviews, applying a structured coding process through Qualcoder to identify key resilience mechanisms, progressing from first-order codes to second-order themes and aggregate dimensions. The findings reveal that while both cooperative and traditional business supply chain networks share similarities in resilience mechanisms, their network structures fundamentally shape how these mechanisms operate, particularly through differences in governance, decision-making, and resource coordination. However, in both types of networks, resilience emerges as an ongoing, adaptive process shaped by crises, internal tensions, and strategic responses. Despite the study’s contributions, its small sample size and cross-sectional design limit generalizability and the ability to capture long-term resilience dynamics. Nevertheless, the findings provide valuable insights for policymakers and organizations supporting artisans to design targeted resilience-enhancing interventions. By shifting the focus from corporate supply chains to small-scale, informal artisanal networks, this study contributes to the literature on supply chain resilience, highlighting the unique adaptive capacities embedded in traditional craftsmanship.